Towards Washable Electrotextile UHF RFID Tags: Reliability Study of Epoxy-Coated Copper Fabric Antennas - Shiqi Wang; Ngai Lok Chong; Johanna Virkki; Toni Björninen; Lauri Sydänheimo; Leena Ukkonen (International Journal of Antennas and Propagation)
We investigate the impact of washing on the performance of passive UHF RFID tags based on dipole antennas fabricated from copper fabric and coated with protective epoxy coating. Initially, the tags achieved read ranges of about 8 meters, under the European RFID emission regulation. To assess the impact of washing on the performance of the tags, they were washed repeatedly in a washing machine and measured after every washing cycle. Despite the reliability challenges related to mechanical stress, the used epoxy coating was found to be a promising coating for electrotextile tags in moist conditions.